CONTRAST-INDUCED ACUTE KIDNEY INJURY AFTER PERCUTANEOUS CORONARY INTERVENTIONS IN PATIENTS WITH STABLE CORONARY ARTERY DISEASE - O. Iu. Mironova; V. V. Fomin (Евразийский Кардиологический Журнал, 2020)
Aim. The aim of the study was to assess the incidence of CI-AKI in patients with stable CAD in 2012 and 2017 respectively.Materials and methods. 1023 patients with stable CAD and indications to the interventions with intraarterial contrast media administration were included in the study. 561 patients were enrolled in the study in 2012 and 462 in 2017 respectively& We conducted a prospective open cohort study (ClinicalTrials.gov NCT04014153). Preventive measures included the administration of 0,9% saline with the speed 1 ml/kg/h intravenously and 0,5 kg/ml/h for the patients with heart failure before and after the procedure. The patients enrolled in 2017 were older, had higher BMI and more risk factors of CI-AKI development. The primary endpoint was the development of CI-AKI.Results. The rate of CI-AKI decreased by more than 3 times in 2017 in comparison with 2012 (6% vs. 18,5% respectively), in spite of the increase of the age of patients, increased use of metformin and higher number of risk factors. The difference was statistically significant (р<0,0001).Conclusion. The prevalence of CI-AKI decreased 3 times in 2017 in comparison with 2012 (6% vs. 18,5% respectively), in spite of the increase of the age of patients and the number of their comorbidities. These results were obtained due to higher level of education of the doctors about the syndrome, preventive measures and methods of treatment.